Important Determinants of Informal Entrepreneurs - Aamar Ilyas; Ramraini Ali Hassan; Waris Ali Khan; Abang Zainoren bin Abang Abdurahman; Syed Muhammad Fahim (2020)
Informal entrepreneurs operate in a shadowy sector where they produce legal goods but do not register their businesses under the requirement of government authorities. Hidden practices of entrepreneurs are a persistent problem for both developed and developing nations. Academic scholars and policymakers considered that public institutes are responsible for this occurrence where taxes rate too high, tough registration procedure with high cost, and political instability are considered significant. In this study, factor model is struggled to investigate the important determinants of informal entrepreneurs. The authors collected survey-based data from 30 markets of Lahore city, provincial capital city of Pakistan. Snowball sampling technique used for picking the respondents because no comprehensive list of informal entrepreneurs is existing in these markets. Sample size was 1200 and 40 structured interviews were conducted in each market with the help of four trained interviewers. Shockingly, this study reveals that not only institutional factors are the most serious but also individual and structural factors are also play a positive role to stay in informal entrepreneurship, at least in developing nations. The outcomes of this study will help policymakers who work to minimize and mitigate the informal activities. Findings verified that individual and structural factors also have a significant role in the development of informal entrepreneurship culture. Government departments and other regulatory agencies can be considered important factors for taking policy decision to minimize the size of such enterprises. This paper is pioneer to factorize the individual, structural, and institutional based determinants to explore the most important reasons for informal entrepreneurs.